Humpback whale (Megaptera novaeangliae) maturity and body condition in Ireland, Norway and Cabo Verde based on UAS photogrammetry data - Blázquez, Miguel; Massett, Nick; O’Callaghan, Seán; Hogan, Marcus; López-Suárez, Pedro; Lopes, Katia; Whooley, Pádraig; O’Brien, Joanne M.; Wenzel, Frederick W.; O’Connor, Ian; Berrow, Simon D. (Frontiers in Marine Science, 2025)
Animal morphometrics are essential for understanding a species’ life history and its ecological interactions with the environment. This study investigates the maturity status and body condition of humpback whales (Megaptera novaeangliae) across understudied areas of the Northeastern Atlantic Ocean. Uncrewed Aerial Systems (UAS or drones) were used to collect photogrammetry data from humpback whales in Ireland, Norway, and Cabo Verde between 2022 and 2024. Body length and condition metrics were derived from aerial imagery and analyzed using Bayesian modeling to estimate and propagate measurement uncertainty. The resulting measurements were evaluated to infer maturity status, migratory patterns, and habitat use. Photogrammetric measurements indicated potential variability in whale body length and condition across study areas, with individuals in Cabo Verde appearing larger and in better condition. In Irish waters, body length was positively correlated with offshore habitat preference, while shorter (younger) individuals tended to inhabit nearshore waters, potentially increasing their exposure to anthropogenic pressures. Additionally, body condition improved intra-seasonally at both the population and individual levels in Irish waters. These findings demonstrate the utility of UAS photogrammetry for assessing the maturity and body condition of humpback whales across diverse habitats. The observed geographical and temporal trends in condition provide valuable insights into habitat use and underscore the importance of Ireland as a feeding ground in the Northeastern Atlantic. This study also highlights the value of UAS photogrammetry in advancing our understanding of baleen whale population ecology in understudied regions, providing relevant information for species conservation and management.